Attitudes towards COVID-19 vaccination and containment measures in Italy and the role of occupational physicians - La Vecchia, Carlo; Alicandro, Gianfranco; Negri, Eva; Scarpino, Vilma; Coggiola, Maurizio; Spatari, Giovanna (La Medicina del Lavoro, 2022)
Background. Vaccine hesitancy is the main barrier to the effective management of COVID-19. This study aims to evaluate attitudes towards vaccination and containment measures in Italy, and the role of occupational physicians in the management of COVID-19. Methods. Between 26 and 31 January 2022, we conducted a national online survey including 1000 respondents (631 workers) representative of the Italian population. A series of questions were asked to get information on attitudes towards COVID-19 vaccination, containment measures and management of COVID-19. Sampling weights were used to obtain national estimates. Results. The majority of respondents (92.6%) received at least two doses of SARS-CoV-2 vaccine (or one dose of Janssen, Ad26.COV2.S), only 4.9% did not get any dose. Most interviewees (79.2%) stated that the decision to be vaccinated was their own choice, while only 4.3% were convinced by the general practitioner or the occupational physician. History of SARS-CoV-2 infection was reported by 23.9% of the participants (30.2% among workers); and 40% of the infected workers were contacted/visited by an occupational physician. Conclusions. Vaccine uptake was remarkably high in Italy. Occupational physicians played a relevant role in the management of COVID-19 in occupational settings